Distribution of mature and newly regenerated nerve fibres after tooth extraction and dental implant placement: An immunohistological study. (27th May 2022) - Li, Jian; Xue, Shenghao; Liu, Zhongning; Yao, Dongyuan; Jiang, Ting
Abstract: Background: The time‐dependent peri‐implant innervation needs to be elucidated in detail. Objectives: To examine the distribution of mature and newly regenerated nerves around the implant with immunofluorescence during 28‐day follow‐up after implantation. Methods: 35 male Sprague–Dawley rats were grouped into non‐operated ( n  = 5), extraction ( n  = 5) and implant ( n  = 25) groups. For rats in the extraction and implant groups, three right maxillary molars were extracted. One month later, a titanium implant was placed into the healed alveolar ridge in the implant group. The implant group was further divided into 5 subgroups according to day 1, 3, 7, 14 or 28 after implantation, on which day serial histological sections were prepared for immunohistochemistry. On day 28, the serial sections were also prepared in the non‐operated and extraction groups. Soluble protein‐100 and growth‐associated protein‐43 were used to immunolabel mature and newly regenerated nerve fibres, respectively. Results: In the peri‐implant soft tissues, the number of both mature and newly regenerated nerves showed an increasing trend in 28 days. In the bone tissues, the number of mature or newly regenerated nerves in both areas at less than 100 μm and 100–200 μm from the implant surface on day 28 grew significantly compared with that on day 1 or 3. In addition, the closest distance from mature nerves to the implant surface decreased evidently. Conclusion: The number of peri‐implant nerves increased in 28 days since implantation. The innervation in the soft tissue took place faster than in the bone tissue. The mature nerves in the bone tissue approached the implant gradually. Abstract : The study observed the time‐dependent changes of mature nerves and newly regenerated nerve fibers around implants in both soft tissues and bone tissues and investigated their role in the development of osseoperception.